1981
DOI: 10.1111/j.1471-0528.1981.tb01032.x
|View full text |Cite
|
Sign up to set email alerts
|

Sclerosing Stromal Tumour of the Ovary Case Report With Endocrine Studies

Abstract: Summary The findings in a patient who was found to have a sclerosing stromal tumour of the ovary associated with a tubal pregnancy are described. Measurement of hormones in blood before and after removal of the tumour suggested the tumour was andro‐gen‐secreting.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
8
0

Year Published

1985
1985
2015
2015

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 32 publications
(8 citation statements)
references
References 14 publications
(9 reference statements)
0
8
0
Order By: Relevance
“…Chalvardjian and Scully1) originally considered ovarian SSTs to be nonfunctioning tumors. However, some investigators have reported endocrine changes associated with secretion of estrogen and progesterone10) as wells as induction of precocious puberty11). Other symptoms include: pelvic pain, a palpable pelvic mass, metrorrhagia and menstrual irregularities including postmenopausal bleeding in elderly patients.…”
Section: Discussionmentioning
confidence: 99%
“…Chalvardjian and Scully1) originally considered ovarian SSTs to be nonfunctioning tumors. However, some investigators have reported endocrine changes associated with secretion of estrogen and progesterone10) as wells as induction of precocious puberty11). Other symptoms include: pelvic pain, a palpable pelvic mass, metrorrhagia and menstrual irregularities including postmenopausal bleeding in elderly patients.…”
Section: Discussionmentioning
confidence: 99%
“…In our series, the patients presented with abdominal pain and/or menometrorrhagia. Most of the tumors are hormonally inactive, but some investigators have described endocrine alterations caused by secretion of estrogen, progesterone, or testosterone9, 10 as well as induction of precocious puberty 11. One of our cases had ascites and elevated CA‐125 levels, which is an uncommon feature of this neoplasm.…”
Section: Discussionmentioning
confidence: 99%
“…Therefore, plasma estrogen, progesterone, androgen, and tumor markers are not specific for the diagnosis of SSTO. An SSTO complicating pregnancy is rare; only a few cases have been reported to date, of which only one case involved an ectopic pregnancy [16]. In that case, an emergency laparotomy revealed a ruptured left ampullary pregnancy and a solid ovarian tumor approximately 3 cm in diameter on the right side; pathological findings confirmed the diagnosis of SSTO [16].…”
Section: Discussionmentioning
confidence: 80%
“…An SSTO complicating pregnancy is rare; only a few cases have been reported to date, of which only one case involved an ectopic pregnancy [16]. In that case, an emergency laparotomy revealed a ruptured left ampullary pregnancy and a solid ovarian tumor approximately 3 cm in diameter on the right side; pathological findings confirmed the diagnosis of SSTO [16]. An SSTO complicating a tubal pregnancy on the same side is also very rare; to date, case 2 in this study is the only reported example.…”
Section: Discussionmentioning
confidence: 99%